Comparing Digital And Manual Translation Proficiencies In English Language Education: An Analysis Of Translation Quality (Program Studi Pendidikan Bahasa Inggris FKIP, 2023)
In this study, we aim to compare the quality of digital and manual translation in English texts for the English Language Education Program. Understanding the strengths and weaknesses of each translation method can help educators improve their teaching strategies and provide better learning outcomes for students. Thus, the research will be guided t the student using in translation between digital and manual translation in English texts for the English Language Education program and the quality of digital and manual translation. , digital translation tools may not capture the nuances and cultural aspects of language that are essential in language learning and communication (Zarei & Gholami, 2020). Manual translation provides a more accurate and nuanced translation than digital tools, as it takes into account context and cultural nuances (Ferraresi & Bernardini, 2019). This study employs a qualitative approach with a comparative method between two translation techniques digital and manual. Data is collected from an abstract of an article with “Pentingnya Pendidikan Bahasa Inggris di Sekolah Menengah” with the original text Bahasa Indonesia then translate it to English language using digital and manual translation. In general, however, studies comparing digital (machine) translation and manual (human) translation in the field of language education have found that while machine translation tools like Google Translate can be helpful for quick and basic translations, they often lack accuracy and precision, particularly in complex or nuanced language tasks.